2021
DOI: 10.24815/siele.v8i3.21218
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of English as a medium of instruction policy in science college programs

Abstract: Achieving science undergraduate programs learning outcomes relies on the students’ proficiency in the language of instruction, a challenge that many policymakers ignore. This study is to understand the influence of English as a medium of instruction (EMI) policy in four undergraduate science programs, namely, Biology, Chemistry, Physics, and Mathematics, in Saudi Arabia. The data were collected from the following groups of participants: 1461 science alumni records, 769 current undergraduate science students’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(35 reference statements)
2
4
1
Order By: Relevance
“…The results showed that both teachers and students agreed on the importance of EMI and the use of English in the Biology study programme; for communication during the teaching-learning and for understanding English-specific terms. The findings aligned with the previous relevant studies (Alhamami & Almelhi, 2021;Simbolon, 2021). The results also confirm other studies showing that EMI implementation is determined by the policy of HE institutions (Dafouz & Smit, 2021;Sahan, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results showed that both teachers and students agreed on the importance of EMI and the use of English in the Biology study programme; for communication during the teaching-learning and for understanding English-specific terms. The findings aligned with the previous relevant studies (Alhamami & Almelhi, 2021;Simbolon, 2021). The results also confirm other studies showing that EMI implementation is determined by the policy of HE institutions (Dafouz & Smit, 2021;Sahan, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast with other findings, academic language-related challenges are significantly predicted by proficiency in the English language (Soruç et al, 2021), English knowledge, and English academic skills (Rose et al, 2020) and showed a better grade point average (GPA) (Alhamami & Almelhi, 2021). However, in this study, the teachers did not purely use EMI in delivering the content to the students as a way to face the challenges.…”
Section: Introductioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Espinas and Fuchs (2022) found that certain MIs meaningfully improve performance in several mathematical domains, providing strong evidence of a linguistic pathway in mathematical development. In the context of undergraduate science programs, Alhamami and Almelhi (2021b) found a strong positive correlation between students’ English proficiency in the first year and their achievement of program learning outcomes as indicated by their cumulative GPA; the researchers concluded that educationalists and program policymakers should direct more attention and interventions toward the MI. In a Spanish context, Block (2022) stressed that the EMI policy is problematic and presents more challenges to students and instructors; Block called for a contrarian and critical view of EMI or “the dark side of EMI.”…”
Section: Literature Reviewmentioning
confidence: 98%